Letter from the Editor - Ika Dewi Ana (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
The field of life sciences moves forward at a rapid pace. Many of us do not fully realize that this acceleration is relatively new phenomenon in the history of mankind. It was in 1990 before the era of wireless phones and laptop computers when J. Craig Venter flew over the ocean and thought inside the airplane about the future of genome projects (as it was written by Ted Anton on his book entitled “Bold Science, Seven Scientists Who Are Changing Our World”).However, just over a short period of time, genome projects, which in 1997 required several years to complete, nowadays take only days. J. Craig Venter stated, as reported by Albert Sasson about the achievements, prospects, and perceptions of medical biotechnology, “For the past 15 years at ever faster rates we have digitizing biology. By that I mean going from the analog world of biology through DNA sequencing into the digital world of the computer. The human genome is perhaps the best example of digitizing biology. Our computer databases are growing faster per day than during the first 10 years of DNA sequencing. Thedatabases have been filling even faster with the results of J. Craig Venter’s global ocean sequencing project. As a result, we have now over 10 million genes in the public databases.” Indeed life sciences progress rapidly.In other areas, nanotechnology, for example, offers new solutions for biomedical sciences and provides a broad technological platform for application in industry. Such applications include bio-processing, molecular medicine, biotechnology, bio-fluidics for handling DNA, and other molecules, etc.Moreover, in another area, regenerative medical therapy reaches the interaction between scaffold, signaling molecules, and cells to enable neo-tissue formation and enhance healing potentials.All the above progresses in life sciences and biomedical sciences improve possibilities for patients to be helped. Meanwhile, ethical problems also arise by the fast science progresses.What about in oral and dental sciences? In some countries, the prevalence of oral and dental diseases is still considered very high. In some other countries the prevalence of dental caries is reducing by the application of fluoridation in societies. Although science has made human beings wealthy and prolonged life span, but to some extent scientists realize the limitation of sciences to cope health problems. In term of oral and dental sciences, opinions arise from research results and the confrontation of them also happens.In view of the overall mapping, The Indonesian Journal of Dental Research is published by The Faculty of Dentistry, Universitas Gadjah Mada, in collaboration with AFDOKGI, The Indonesian Association of The Faculty of Dentistry. The Indonesian Journal of Dental Research is an international journal dedicated to the latest advancement of dental research in Indonesia and Asia Pacific regions. The goal of this journal is to provide a platform for dentists and academicians all over the world to promote, share, and discuss various new issues and developments in different areas of dental and oral sciences.The acceptance of manuscripts will not rely on opinions of editors, but on evidence-based logical facts. The editors will help authors to improve their manuscripts by scientific bases. Any kind of articles are welcomed within the aim and scope of this journal.We are waiting for your contributions.Ika Dewi AnaEditor in Chief